PENGARUH CITA RASA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI AISY DRINK KOTA BIMA (Studi Konsumen Di Aisy Drink) - Anita Anita; Wulandari Wulandari (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2021)
Continuing relationships with old customers and continuing to acquire new customers with the concept of customer satisfaction will have a greater influence on the market share. In the city of Bima, there are many culinary places, one of which is AISY DRINK. Aisy Drink has a unique product taste that is ready to accompany your day with different flavor variants. This study aims to determine the effect of taste (X1), motivation (X2) on purchasing decisions (Y). The study was conducted on 96 consumers as a sample with data analysis techniques, namely classical assumption test, multiple linear regression, correlation coefficient, determination, t test and F test. consumer purchasing decisions at Aisy Drink Bima City. Based on simultaneous results (F) where the value of Fcount is 38.0005>Ftable (38.0005>3.09) and with a sig. value of 0.000<0.05 so it can be concluded that the taste( X1) and Promotion (X2) together have a positive and significant effect on consumer purchasing decisions (Y).